1981
DOI: 10.1210/jcem-53-4-730
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxytocin Concentrations in Men, Nonpregnant Women, and Pregnant Women before and during Spontaneous Labor*

Abstract: Baseline plasma oxytocin (OT) concentrations were measured in 25 healthy men, 102 nonpregnant women, and 59 pregnant women from 15-42 weeks gestation. In addition, plasma OT levels were measured at the onset, peak, and immediately after a single uterine contraction in 6 women in the latent phase and 14 women in the active phases of labor, as well as in 19 women at initial presentation of the fetal head on the perineum (+3 station) and 11 women at the time of delivery of the head during a normal vaginal deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(71 citation statements)
references
References 20 publications
5
65
0
1
Order By: Relevance
“…2) found in this study are within the range of the low predelivery values found in most recent studies (Leake et al 1981, Fuchs et al 1991, Thornton et al 1992, OT plasma levels seem to rise only during delivery by an increase in pulse frequency and duration. Np-OT, measured in this study, was determined by subtraction assay and is considered to be an index of endogenous oestrogens (Legros & Grau 1973).…”
Section: Discussionsupporting
confidence: 90%
“…2) found in this study are within the range of the low predelivery values found in most recent studies (Leake et al 1981, Fuchs et al 1991, Thornton et al 1992, OT plasma levels seem to rise only during delivery by an increase in pulse frequency and duration. Np-OT, measured in this study, was determined by subtraction assay and is considered to be an index of endogenous oestrogens (Legros & Grau 1973).…”
Section: Discussionsupporting
confidence: 90%
“…Although in rodents, OT is believed to play a significant role in the initiation and maintenance of parturition [13,23], in humans, circulating OT does not seem to be essential for the initiation and maintenance of labour [24]. Normal parturition has been observed in the absence of OT in mice [24] as well as in cases of clinical pituitary gland dysfunction [25] and the concentrations of maternal or fetal OT does not increase with the onset of or during labour [26].…”
Section: Previously Established Roles Of Ot/otr Systemmentioning
confidence: 99%
“…Nevertheless, the pituitary may provide the source of oxytocin since a basal level of oxytocin was measurable in human serum throughout pregnancy (Leake et al 1981) and a low pulsatile secretion of oxytocin was also found in pregnant cows (Fuchs et al 1986).…”
Section: Figurementioning
confidence: 99%